Parenting Paradigms in Islamic Educational Philosophy: Reconstructing The Concept of Parenting Amidst The Challenges of Modernity - Rahayu, Evi (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2026)
This study examines parenting paradigms in Islamic educational philosophy and reconstructs the concept of parenting amidst the challenges of modernity, particularly in the digital era. The research adopted a qualitative approach with a multi-family case study design involving Muslim families in two major cities in Indonesia who actively use digital technology and have pre-teen children. Data collection was conducted through in-depth interviews, participant observation, and document analysis, while thematic analysis was employed to identify recurring patterns and themes. The findings reveal that Muslim families employ various adaptive strategies in child-rearing within the digital age. First, 85% of families maintain regular congregational prayers, and 70% allocate specific time for Quran study, positioning the home as the "first school" (madrasah al-ula). Second, active parental involvement in guiding children's digital media usage shows a positive correlation with children's understanding of Islamic digital ethics. Third, behavioural role modelling (uswah hasanah) is effective in instilling Islamic values, as children understand these values more easily by observing parental practices. Fourth, parents demonstrate a paradigm shift by strategically using technology to support religious learning through educational applications and Islamic content. The study identifies time constraints and negative digital media impacts as primary challenges. The research concludes that Islamic educational philosophy provides a solid framework for relevant and adaptable parenting practices, emphasising the integration of moderation, moral character, and Islamic identity preservation. Collaboration between parents, educators, and communities is essential for developing spiritually and digitally resilient generations capable of navigating the complexities of the digital world responsibly.